In vitro and in vivo investigation of the biological and mechanical behaviour of resin-modified glass-ionomer cement containing chlorhexidine - De Castilho, Aline Rogéria Freire; Duque, Cristiane [UNESP]; Negrini, Thaís de Cássia [UNESP]; Sacono, Nancy Tomoko [UNESP]; De Paula, Andréia Bolzan; Costa, Carlos Alberto de Souza [UNESP]; Spolidório, Denise Madalena Palomari [UNESP]; Puppin-Rontani, Regina Maria (Elsevier, 2013)
Objectives: To evaluate: (1) the in vitro antibacterial, cytotoxic and mechanical properties of a resin-modified glass ionomer cement (RMGIC) containing different concentrations of chlorhexidine (CHX) and (2) the in vivo microbiologic action of the best concentration of CHX associated with the RMGIC applied on remaining dentine after indirect pulp treatment (IPT). Methods: For the in vitro studies, RMGIC was associated with 0.2, 0.5, 1.25 and 2.5% CHX. Microbiologic evaluation consisted of an agar diffusion test on cariogenic bacteria for 24 h. Odontoblast-like cell metabolism and morphology analyses measured the cytotoxic effects of the RMGIC groups after 24 h. The same groups were submitted to compressive and diametral tensile strength. The in vivo treatment consisted of IPT using an RMGIC associated with the best CHX concentration. Clinical and microbiologic evaluations were performed before and after 3 months. Results: The use of 1.25% CHX significantly improved the antibacterial effects of the evaluated RMGIC, without causing any detrimental effects to the odontoblast-like cells and on the mechanical properties. This RMGIC and CHX combination completely eliminated mutans streptococci after 3 months of IPT. Conclusion: The RMGIC and 1.25% CHX mixture showed great biological and mechanical behaviour and could be a good treatment against caries progression. Clinical significance: The association of CHX with a liner RMGIC opens a new perspective for arresting residual caries after IPT. © 2012 Elsevier Ltd. All rights reserved.
Keywords: Antibacterial activity; Cell culture; Chlorhexidine digluconate; Glass ionomer cement; Indirect pulp therapy; Mechanical properties